(untitled) (Canadian Journal of Native Studies, 2026)
Abstract Findings presented in this study show that competition in the four most recent Navajo Nation Presidential General Elections, the second round in the non-partisan majority run-off electoral system, reflect choices made about specific candidates, with concentrations of support for Jonathan Nez and opposition to Joe Shirley Jr., rather than a ‘nationalizing’ trend toward reduced competition at the national and chapter levels of government. Voter support for repeat candidates in the Primary Election or first round contests is revealed to be weak. However winning candidates in the General Election perform well in chapters where they performed well in the Primary Election.